Marie Bach, Ole Degn, Poul Strømstad: Denmark. Køge 1500-1950. (Scandinavian Atlas of Historic Towns, 7). (Odense Universitetsforlag, 1993). 106 s., 31 kort. - Poulsen, Bjørn (Historie/Jyske Samlinger, 1996)
-